2017
DOI: 10.1111/2041-210x.12854
|View full text |Cite
|
Sign up to set email alerts
|

Classifying ecosystems with metaproperties from terrestrial laser scanner data

Abstract: In this study, we introduce metaproperty analysis of terrestrial laser scanner (TLS) data, and demonstrate its application through several ecological classification problems. Metaproperty analysis considers pulse level and spatial metrics derived from the hundreds of thousands to millions of lidar pulses present in a single scan from a typical contemporary instrument. In such large aggregations, properties of the populations of lidar data reflect attributes of the underlying ecological conditions of the ecosys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 12 publications
2
10
0
Order By: Relevance
“…Previous studies have focused on comparisons of ALS and TLS at a single site or forest type in a localized region, but consistent with our results, these have found that ALS and TLS are comparable in their capacity to delineate features such as canopy height, cover, and vertical stratification [23][24][25][26]. TLS systems are a well-established method to provide high resolution, functionally meaningful measurements of structural diversity in forest ecosystems at the stand-scale [2,19,20,22,25,35], but these results demonstrate that ALS could potentially be used to scale the characterization of canopy structural diversity to much broader spatial extents.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Previous studies have focused on comparisons of ALS and TLS at a single site or forest type in a localized region, but consistent with our results, these have found that ALS and TLS are comparable in their capacity to delineate features such as canopy height, cover, and vertical stratification [23][24][25][26]. TLS systems are a well-established method to provide high resolution, functionally meaningful measurements of structural diversity in forest ecosystems at the stand-scale [2,19,20,22,25,35], but these results demonstrate that ALS could potentially be used to scale the characterization of canopy structural diversity to much broader spatial extents.…”
Section: Discussionsupporting
confidence: 88%
“…LiDAR is a useful tool for the multi-dimensional characterization of forest structure that has versatile terrestrial and aerial deployment platforms spanning a multiple of spatial extents and resolutions [14][15][16][17][18]. Terrestrial laser scanners (TLS) and aerial laser scanners (ALS) have both been shown to be effective at quantifying components of forest structural diversity [14][15][16][17][18][19][20], however, each LiDAR platform has trade-offs for data resolution and spatial coverage. TLS and ALS scan the forest from opposite angles and occlusion by the canopy constrains the capacity of each to obtain data from portions of the canopy distal to the instrument [21] (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…1a; Whittaker 1970). These vegetation structural types can be viewed as an agglomeration of canopy traits describing the arrangement of vegetation elements in canopy space and generally relate to three primary components of variation: canopy height, vertical layering and horizontal openness/patchiness (Aber et al 1982;Brokaw & Lent 1999;Ehbrecht et al 2016;Paynter et al 2018;Cushman & Kellner 2019), as well as higher-order metrics that combine or describe variation in these traits to characterise the arrangement of canopy elements in two-dimensional (2D) or 3D space (Hardiman et al 2011;Chen et al 2012;Seidel et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…TLS observations in HF have been used to demonstrate the ability of lidar instruments to be sensitive to the ecosystem type and condition of the scanned space. CBL scans from HF have shown promise in separating distinctly different forest structures by using the method of metaproperties analysis to distil aggregate statistics from the geometry and pulse properties of the data [ 25 ]. Furthermore, expensive, high-resolution scanners are not necessary for such scan-based techniques.…”
Section: Discussionmentioning
confidence: 99%